A one-step PCR-based method for specific identification of 10 common lactic acid bacteria and Bifidobacterium in fermented milk. (February 2015) - Lu, Wenwei; Kong, Wentao; Yang, Pu; Kong, Jian
Abstract: A one-step PCR-based method was constructed for the rapid detection of 10 common lactic acid bacteria (LAB) and Bifidobacterium . Ten primer pairs were designed based on the sequences that specify the 16S rRNA genes of Lactococcus lactis subsp. lactis, Lactococcus lactis subsp. cremoris, Streptococcus thermophilus, Lactobacillus delbrueckii subsp . bulgaricus, Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus fermentum, Lactobacillus helveticus, Bifidobacterium and Leuconostoc . The primers showed high specificity for target species. The detection limit was 10 4 –10 5 cfu mL −1 for Lb. delbrueckii and 10 3 –10 4 cfu mL −1 for the others. This method was applied to identify the species mentioned above, in situ, from 8 samples of traditional fermented milk, and monitor the constitution of the species in commercial dairy yoghurt. The results were consistent with the results of 16S rRNA sequencing, suggesting that the method was reliable for the rapid identification of LAB and Bifidobacterium used in fermented milk.